An oxanthroquinone derivative that disrupts RAS plasma membrane localization inhibits cancer cell growth - Tan, Lingxiao (J Biol Chem, 2018)
Oncogenic RAS proteins are commonly expressed in human cancer. To be functional, RAS proteins must undergo post-translational modification and localize to the plasma membrane (PM). Therefore, compounds that prevent RAS PM targeting have potential as putative RAS inhibitors. Here we examine the mechanism of action of oxanthroquinone G01 (G01), a recently described inhibitor of KRAS PM localization. We show that G01 mislocalizes HRAS and KRAS from the PM with similar potency and disrupts the spatial organization of RAS proteins remaining on the PM. G01 also inhibited recycling of epidermal growth factor receptor and transferrin receptor, but did not impair internalization of cholera toxin, indicating suppression of recycling endosome function. In searching for the mechanism of impaired endosomal recycling we observed that G01 also enhanced cellular sphingomyelin (SM) and ceramide levels and disrupted the localization of several lipid and cholesterol reporters, suggesting that the G01 molecular target may involve SM metabolism. Indeed, G01 exhibited potent synergy with other compounds that target SM metabolism in KRAS localization assays. Furthermore, G01 significantly abrogated RAS-RAF-MAPK signaling in Madin-Darby canine kidney (MDCK) cells expressing constitutively activated, oncogenic mutant RASG12V. G01 also inhibited the proliferation of RAS-less mouse embryo fibroblasts expressing oncogenic mutant KRASG12V or KRASG12D but not RAS-less mouse embryo fibroblasts expressing oncogenic mutant BRAFV600E. Consistent with these effects, G01 selectively inhibited the proliferation of KRAS-transformed pancreatic, colon, and endometrial cancer cells. Taken together, these results suggest that G01 should undergo further evaluation as a potential anti-RAS therapeutic.